Ty1-copia group retrotransposons are ubiquitous and heterogeneous in higher plants. - Flavell, A J (1992)
We have used the polymerase chain reaction to isolate fragments of Ty1-copia group retrotransposons from a wide variety of members of the higher plant kingdom. 56 out of 57 species tested generate an amplified fragment of the size expected for reverse transcriptase fragments of Ty1-copia group retrotransposons. Sequence analysis of subclones shows that the PCR fragments display varying degrees of sequence heterogeneity. Sequence heterogeneity therefore seems a general property of Ty1-copia group retrotransposons of higher plants, in contrast to the limited diversity seen in retrotransposons of Saccharomyces cerevisiae and Drosophila melanogaster. Phylogenetic analysis of all these sequences shows, with some significant exceptions, that the degree of sequence divergence in the retrotransposon populations between any pair of species is proportional to the evolutionary distance between those species. This implies that sequence divergence during vertical transmission of Ty1-copia group retrotransposons within plant lineages has been a major factor in the evolution of Ty1-copia group retrotransposons in higher plants. Additionally, we suggest that horizontal transmission of this transposon group between different species has also played a role in this process.